Aspectos da ontogenia, ginosporogênese e ginogametogênese em Dasyphyllum brasiliense (Spreng.) Cabrera e Schlechtendalia luzulaefolia Less. (Barnadesioideae-Asteraceae) - Costa, Patrícia Kurtz da (2014)
Asteraceae has attracted many embryologists because of its high variability of the embryological features. Nevertheless, nothing is known about the embryology of the species basal subfamily, Barnadesioideae. Thus, this paper aims to describe the processes of ginosporogenesis and ginogametogenesis in two species of Barnadesioideae, Sclechtendalia luzulaefolia, considered basal and sister to the other species that belong to family and Dasyphyllum brasiliense whose genus was also sometimes considered basal. Both species are native to Rio Grande do Sul. S. luzulaefolia was collected in São Pedro do Sul, RS, Brazil and D. brasiliense in Santa Maria, RS, Brazil and in São Pedro do Sul, RS, Brazil. The corolla is the first floral whorl to arise in both species, followed by the androecium, gynoecium and calyx in S. luzulaefolia; calyx, androecium and gynoecium in D. brasiliense. Tenuinucellate incomplete ovule, asymmetric integument and dual origin endothelium (funicule and integument) are new results for Asteraceae. The archesporium is usually unicellular, but ovules with two archesporial cells were observed. In S. luzulaefolia two types of tetrad are present, the linear tetrad being more commom than the tetrad with paired ginospores. The ginophyte development pattern in D. brasiliense can be an indication of its derived position in Barnadesioideae, since it has bisporic ginophyte of the Allium type and in S. luzulaefolia where ginophyte is monosporic of the Polygonum type, integrating these features simultaneity of mitotic cycles and cellularization of ginófito. The mature ginophyte is 4-cell, in both species, because of the degeneration of the antipodes, which can configure a plesiomorphic character for the family. The synergids extend into the micropile canal and they have fibrillar apparatus of typical morphology for Asteraceae. Labyrinthine walls of the middle cell and flange type wall thickening are present only in S. luzulaefolia in cells of the endothelium and micropilar canal. Therefore, common characteristics were identified for S. luzulaefolia and D. brasiliense which may be considered basal for Asteraceae and diagnostic for Barnadesioideae, as well as embryological characters that corroborate the position derived from D. brasiliense in this subfamily.